Connecting Active Reading and Academic Writing in A Multicultural Context: Strategies for Syllabus and Material Packet Development - Iftanti, Erna; Awalin, Arpinda Syifa’a; Amrullah, Latif (Dinamika Ilmu, 2025)
In response to the absence of a module for academic writing courses in a multicultural classroom context and the problems of starting to write and finding ideas for academic writing, this research aims to develop an academic writing module that meets the teachers' and undergraduate students' needs and voices. This study employed ADDIE model of R&D carried out through some steps: need analysis, drafting, developing, implementing, and evaluating. In the steps of need analysis, students claimed that reading contributes to getting ideas and building background knowledge of a certain topic for writing. Brainstorming is another voice they proposed to solve the problems. Moreover, they believe that writing essays can be the starting point for writing journal articles. Accordingly, by considering all findings in the initial step, the products of this R&D comprise students’ and teachers’ books. The product's specific characteristics are reading preceding essay writing, brainstorming, the syllabus, the scoring rubric with a detailed description, and academic honesty. The study revealed that integrating active reading into academic writing modules can be pedagogically implemented and enhance both students’ reading and writing skills. The following studies on developing a module for other levels of education can be carried out to further contribute to reading-writing pedagogy.